A netnography examination of tripadvisor reviews: A case study of the St Regis Hotel Kuala Lumpur - Izyanti Awang Razli; Mohd Noor Ismawi Ismail; Sharifah Damiah Husna Syed Amir Shah; Hanisah Ismail (Penerbit UMT, 2021)
There has been a growing reliance on consumer generated content as a source of knowledge for hospitality product decision-making. People post their views, ratings, and reviews of products and services on such platforms, and companies and research organizations are interested in analyzing and extracting all of the comments. It is critical for hotels to take advantage of online customer review information in order to better understand their customers and enhance hotel efficiency. However, analyzing guest reviews is challenging as it contains abundance of data. Using The St Regis Kuala Lumpur as a case study, the objective of the paper is to profile the hotel online reviews using a Netnography approach, identify the hotel attributes that guest comment based on the hotel online reviews and examine the guest satisfaction attitude based on the hotel online reviews. A total of 388 reviews from TripAdvisor were collected. The findings revealed that most of the hotel guests who left comments were international tourists, and couples. Many of whom left excellent ratings for the hotel. The findings show there are nine attributes that are frequently mentioned namely, amenities, location, price, service, cleanliness, food and beverages, hotel and room environment. The results also show that guests left both positive and negative reviews in few common categories such as hotel cleanliness, hotel environment and amenities. Among all the attributes mentioned, satisfied guests tended to leave positive comments for things like hotel cleanliness, hotel and room environment, while dissatisfied guests emphasised the amenities or the lack thereof. The findings of this study make several theoretical and managerial inferences with regards to identifying hotel attributes that contribute to guest satisfaction and improves the understanding of what satisfies and dissatisfies guests from the comments left by the guests on TripAdvisor. The paper concludes with limitations and suggests future research.